The study of extension performance and tea market opportunities to successful of tea farmer groups at Sodonghilir District, Tasikmalaya Regency - Sita, Kralawi (Research Institute for Tea and Cinchona, 2015)
The good performance of extension activities and openness tea market opportunities has been playing an important role in accelerate the successful of tea farmer groups. The successful of tea farmer groups itself can be seen from the functioning of the units in farmer group activities, namely unit of study, unit of production, unit of collaboration, and unit of business. This study are aimed to determine the successful of tea farmer groups in carrying out its functions and to determine the effect of extension performance and tea market opportunities to the successful of the tea farmer groups at Sodonghilir District, Tasikmalaya Regency. This study used mixed method approach with sequential explanantory strategy that analyzed by using path analysis. The sampling method that used in this study was proportional random sampling with 56 farmers or 25% of the sample population (225 farmers). The results show that the highest successful of tea farmer groups at Sodonghilir District on unit of production, unit of collaboration, and unit of business were still low. Extension performance and tea market opportunitiest significant influenced directly to the successful of tea farmer groups. The better extension performance and greater tea market opportunities, so the higher the successful of farmer groups. The efforts to increase the successful of tea farmer groups can be done by increasing the institutional capacity of tea smallholders, extension performance, and disclosure opportunities of policy and tea market.